The use ODLM method to increase student's activity and learning outcomes in geometry - Aini, Fathiya Nur; Marzuki, Ismail (Universitas Riau Kepulauan, 2023)
Ineffective learning activities and lack of learning innovation can be the cause of low learning outcomes and lack of student activity. This research aims to investigate the effects of using OdLM methods in learning mathematics in elementary school. Through this research, it is hoped that empirical evidence can be found regarding increasing student activity in the learning process and its impact on learning outcomes in geometry This research uses a classroom action research (PTK) approach with the Kemmis and Mc Taggart model where each cycle consists of four steps,, namely planning, action, observation, and reflection. The research instruments used were observation sheets and written tests. This research data analysis uses qualitative descriptive. The research results showed that students' activities and learning outcomes increased after implementing OdLM in Cycle I, obtaining an average score of 65% (high) and in Cycle II it increased to a score of 73% (high). Meanwhile, students' learning outcomes in Cycle I received an average score of 66.67% -72.22%, then in Cycle II it was 100%. It can be said that the application of OdLM methods can increase the activities and learning outcomes of elementary school students.